Komatiites From Mantle Transition Zone Plumes - Wyman, Derek (Frontiers in Earth Science, 2020)
During the Archean, periods of volcanism on both individual cratons and globally occurred sporadically between long periods of volcanic inactivity. The episodic volcanism commonly included both plume- and arc-type magmatism, raising the issue of a possible link between “bottom up” and “top down” geodynamic processes. Rather than being cases of plume-initiated subduction, the best-preserved cratons demonstrate that komatiitic magmatism postdated at least some of the subduction-linked volcanism. Several factors suggest that komatiite-generating plumes may have been sourced in the mantle transition zone. Komatiites contain 0.6 wt. % or more H2O, which is contrary to earlier predictions for plume ascent through through the transition zone. Geodynamic reconstructions indicate that multiple subducted slabs penetrated the transition zone in the region of future plume ascent and the related trench configurations limit the size of any associated plume heads. The implied size of the plume heads is inconsistent with that required for a plume to ascend from the core-mantle boundary but matches that predicted for plumes sourced from the lower transition zone. Transition zone plumes have mainly been advocated for two types of geodynamic scenarios. They are common in post-Archean “big wedge” scenarios involving the consequences of subducted slabs that stall at the base of the transition zone and they are also an outcome of the “basalt barrier” featured in some geodynamic models for the Archean and early Proterozoic. The latter models suggest that the basaltic components of Archean subducted slabs were too buoyant to descend into the lower mantle and formed a boundary layer that isolated the upper mantle and lower mantle on the early Earth, except in times of mantle overturns. The basalt barrier was a significant thermal boundary layer that, in principle, could act as the nucleation site of upwelling plumes anywhere on the globe. The evidence discussed here, however, suggests that the mainly peridotitic mantle upwellings were enhanced by the nearby injection of closely associated slabs into the transition zone.